Assolutizzazione dell’umano e imprigionamento antropomorfico del divino. Neri e il dualismo (Materiali di Estetica. Terza serie, 2016)
Neri’s way of criticizing Banfi’s late philosophical position is most interesting in order to reason on the negative consequences of overcoming the dualistic relationship between the dimension of the ideal and the dimension of the real.